Balanced Scorecard Sebagai Alternatif Tool Sistem Manajemen Sekolah Abad 21 - Miftahul Huda; Rhoni Rodin (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
This paper aims to analyze the balanced scorecard as an alternative tool for school management systems in the 21st century as it is today. This research uses a qualitative approach with descriptive analysis. Data collection techniques carried out by literature review / literature study relating to the concept of balanced scorecard and school management. The results showed that the concept of balanced scorecard is not only used for work measurement systems, but also used as a management system. This Balanced Scorecard can be used for the development of measurement systems as well as a means, which essentially involves the management system, especially strategic management. The balanced scorecard is a management tool that translates the organization's vision, mission and strategy into a comprehensive set of performance measurements to produce an organizational performance measurement framework through several perspectives: financial, customer, internal business processes, and learning and growth.